Comprehensive analyses reveal the promising value of gasdermins as prognostic biomarkers and immunotherapeutic targets in head and neck squamous cell carcinoma - Huageng Huang; Jingjing Ge; Shunzhen Lu; Xinyi Deng; Ying Tian; He Huang; Zhao Wang; Yuyi Yao; Huangming Hong; Tongyu Lin (Heliyon)
Background: In several studies of head and neck squamous cell carcinoma (HNSC), the regulation of tumorigenesis and therapeutic sensitivity by pyroptosis has been observed. However, a systematic analysis of gasdermin family members (GSDMs, including GSDMA/B/C/D/E and PJVK), which are deterministic executors of pyroptosis, has not yet been reported in HNSC. Methods: We performed comprehensive analyses of the expression profile, prognostic value, regulatory network, and immune infiltration modulation of GSDMs in HNSC on the basis of a computational approach and bioinformatic analysis of publicly available datasets. Results: A total of 18.65 % (94/504) of HNSC patients harbored GSDM alterations, with the most dominant type being amplification. Compared with those in normal tissues, the mRNA and protein levels of GSDMs, especially GSDMD/E, were commonly elevated in HNSC (P < 0.05). Additionally, the expression of GSDMs differed significantly between the clinicopathological subgroups of HNSC patients. Overall survival of HNSC patients benefited from increased GSDMC expression (HR = 0.67, P = 0.0053) and decreased GSDME expression (HR = 1.42, P = 0.0140). Regulatory network analysis revealed several essential biological processes associated with GSDMs, including positive regulation of cytokine production involved in the immune response. Notably, almost all infiltrating immune cells and immune checkpoints were negatively correlated with GSDMA/C/E expression and positively related to GSDMB/D and PJVK expression. Conclusions: We indicated the potential role of GSDMs (especially GSDME) in HNSC pathogenesis, progression and response to immunotherapy, providing important evidence for further prospective studies and molecular mechanism exploration.